Modification of non-woven cellulose for medical applications using non-equlibrium gassious plasma - Stana-Kleinschek, Karin (Materiali in tehnologije, 2011)
This paper presents the use of a non-equilibrium gaseous plasma technique for the activation of regenerated non-woven cellulose, as used in the preparation of wound-dressing materials. Plasma technology provides surface modification according to the required quality in terms of speed, homogeneity, process stability, and efficiency. In this study the non-woven cellulose was exposed to oxygen plasma (O2) in order to acquire the natural polymer's super-hydrophilicity which, among others, defines the materials' usability forwound-dressing. The influence of the plasma parameters on the material's hydrophilicity was studied; and the optimal plasma conditions defined. Combinations of different experimental techniques (contact angle, water retention value, and moisture content) were studied and correlated with the mechanical properties, as a function of plasma modification. The specific adsorption capacity of the non-woven cellulose using oxygen plasma treatment was achieved. In the next step, this material with increased hydrophilicity and improved mechanical properties will be used in the preparation of multilayered wound-dressing materials for specific functionalities (incorporation of drugs, specific functional properties).
Keywords: regenerirana celulozna vlakna; sanitetni material; mehanske lastnosti